Diagnostics of lateral support syndrome of the patellofemoral joint - Kurtyka, Daria; Dziarkowski, Dariusz; Gawrych, Szymon; Różański, Gracjan; Dobosiewicz, Anna Maria; Badiuk, Nataliia (Journal of Education, Health and Sport, 2018)
The lateral support syndrome of the patella and thigh joint is classified as a kind of dysplasia of this joint. The causes may be a muscular balance disorder, congenital abnormalities in the locomotor system or posture defects. Lateral support syndrome is most easily diagnosed through physical and subjective examination of the patient, while imaging is the best method to determine the exact type and scale of the abnormality.